Where Is Literary Teaching Going? - Garayalde, Nicolás (2023)
The science of literature that emerged at the end of the 19th century shaped a literary teaching framed in the culture of commentary, whose salient feature was the division of languages, for the dissertation was not to be written in the form of its object. This division of languages led to an instrumentalisation of literature, where the literary text is used to reproduce a knowledge that is already known. In recent decades, as a reaction to this teaching, pedagogies have emerged (humanist or pleasure pedagogies) that aim at a direct contact with the work, a contact stripped of theory. It seems that these pedagogies are rushing towards epistemologically naïve forms of knowledge. Consequently, as I propose in this essay, literary teaching should move towards a teaching articulated in two dimensions: 1) an epistemology of reading; 2) a teaching of the writing of reading that returns to rhetorical culture.